PENGARUH BEBAN KERJA DAN STRES KERJA TERHADAP PRODUKTIVITAS KERJA KARYAWAN DENGAN MOTIVASI KERJA SEBAGAI VARIABEL INTERVENING DI POLTEKKES KEMENKES SURAKARTA JURUSAN ORTOTIK PROSTETIK - Nadiaty, Afia Halida; Wahyudi, Amin; Sriwidodo, Untung (Universitas Slamet Riyadi, 2019)
This research is conducted to know the significancy between: (1) Workload to the Work motivation; (2) Job stress to the Work motivation; (3) Workload to the productivity; (4) Job stress to the wards productivity; (5) Work motivation to the productivity; (6) Workload to the productivity with Work motivation as an intervening variable; (7) Job stress to the productivity with Work motivation as an intervening variable in the Polytechnic of the Kemenkes Surakarta Department of Prosthetic Orthotics. The population is the employee of the Polytechnic of the Kemenkes Surakarta Department of Prosthetic Orthotics 2019 as many as 32 persons. Samples were taken by total sampling of 32 people. The technique of gathering the data is using inquiry sheet validity test and reliability test. The analysis technique uses double regression with classical assumption. The conclusion of the research; (1) Workload has a negative and significant effect on Work motivation. (2) Job stress has a negative and significant effect on Work motivation. (3) Workload has a negative and significant effect on productivity. (4) Job stress has a negative and significant effect on productivity. (5) Work motivation has a positive and significant effect on productivity. (6) Work motivation mediates the effect of workload on productivity. (7) Work motivation mediates the effect of work stress on productivity.